Electronic Characteristics of Layered Heterostructures Based on Graphene and Two-Dimensional Perovskites: First-Principle Study - Lev Zubkov; Pavel Kulyamin; Konstantin Grishakov; Savaş Kaya; Konstantin Katin; Mikhail Maslov (Colloids and Interfaces)
Layered perovskites have been actively studied due to their outstanding electronic and optical properties as well as kinetic stability. Layered perovskites with hexagonal symmetry have special electronic properties, such as the Dirac cone in the band structure, similar to graphene. In the presented study, the heterostructure of single-layer all-inorganic lead-free hexagonal perovskite of the A3B2X9 type (A = Cs, Rb, K; B = In, Sb; X = Cl, Br) and graphene (Gr) was studied. The structural and electronic characteristics of A3B2X9 and the A3B2X9/Gr composite were calculated using density functional theory. It was found that graphene is not deformed, while the main deformation is observed only in perovskite. B-X bonds have different sensitivities to stretching or compression. The Fermi level of the A3In2X9/Gr composite can be shifted down from the Dirac point, which can be used to create optoelectronic devices or as spacer layers for graphene-based resonant tunneling nanostructures.